Diffusion of PV in Japan and Germany-Role of Market-Based Incentive and Research and Development (R&D) Investment - Chowdhury, Sanjeeda; Sumita, Ushio (Journal of Technology Innovations in Renewable Energy, 2013)
The goals of increasing the use of PV energy face significant obstacles. Regulatory requirements can be used to mandate the adoption of renewable energy, but market-based incentive mechanisms can also achieve the same results by inducing voluntary behavior from stakeholders. Variations in terms of both design and implementation of market-based incentives can have meaningful effects on the outcomes of incentive programs. We examine Japan and Germany in which PV energy accounts for a relatively high portion of total net electricity energy consumption. Germany FITs were originally linked to the spot electricity price, but a fixed tariff was adopted in 2000, and revised in 2004. A grant program also funds a portion of construction costs for new PV systems. The country has experienced rapid uptake of renewables over the past decade, making it a world leader in solar PV at the end of 2008. The purpose of this study is to analyze the PV diffusion in Japan and Germany during 1990-2011. Germany chooses an effective market-based incentive mechanism which is long term and more generous than Japanese incentive program. The termination of incentive policy is the main blocking factor of the decline of PV market in Japan.